THE INFLUENCE OF WORK-LIFE BALANCE AND PERCEPTIONS OF EMPLOYEE RELATIONS ON THE WELL BEING OF GENERATION Z EMPLOYEES IN THE CITY OF BANDUNG - Elsa Hasna Riskian; Mukaram Mukaram (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2025)
PURPOSE - Finding out how work-life balance and employee relations perspectives impact the wellness of Generation Z employees in Bandung is the aim of this study.METHODOLOGY - The quantitative research methodology makes use of two data analysis techniques: multiple linear regression and descriptive statistics. Questionnaires were sent as part of the data collection methods. The sample used amounted to 222 respondents. Sampling using purposive sampling with the criteria of Generation Z employees who have worked for at least 6 months.FINDING - According to the study's findings, work-life balance and opinions about employee interactions both significantly and favorably impact workers' well-being